Age of Majority and Alternatives to Guardianship: A Necessary Amendment to the Individuals with Disabilities Education Improvement Act of 2004. (June 2023) - Raley, Sheida K.; Shogren, Karrie A.; Martinis, Jonathan; Wehmeyer, Michael L.
Federal law requires that schools provide students receiving special education services and their parents/guardians with notice, 1 year before the student reaches the age of majority, that all of the educational rights previously afforded to the parents/guardians will transfer to the student once they reach the age of majority. During this "transfer-of-rights" period, educational professionals often advise parents/guardians to seek legal guardianship over the student with disabilities without providing information about other options. As a result, many parents/guardians seek guardianship without knowing about or exploring less-restrictive alternatives that could help students retain their legal rights, provide opportunities to enhance self-determination, and build community participation skills that benefit them in school and as adults. This article will (a) provide an overview of the use and impact of guardianship and describe recent advances in developing and implementing less-restrictive alternatives to guardianship and (b) advocate for an amendment to the Individuals with Disabilities Education Improvement Act of 2004 that will require schools to provide students and their families with information about the full range of decision-making options during the "transfer-of-rights" period.